Iron-Deficiency Anemia Leading to Transient Ischemic Attacks due to Intraluminal Carotid Artery Thrombus - H. Z. Batur Caglayan; B. Nazliel; C. Irkec; A. Dumlu; A. Filiz; M. Panpalli Ates (Case Reports in Neurological Medicine)
Reactive thrombocytosis secondary to iron-deficiency anemia (IDA) is a rare but recognized cause of stroke. We report the case of a patient with iron-deficiency anemia presenting with multiple transient ischemic attacks (TIA) due to intraluminal thrombus of an internal carotid artery. The putative mechanisms underlying anemia and stroke syndromes are not completely understood, and it is believed that iron deficiency may cause ischemic stroke by several potential mechanisms. Thrombocytosis is often associated with iron deficiency, and microcytosis produces a reduction in the red cell deformability and could produce a hypercoagulable state. The platelet count and function observed in iron-deficiency anemia could act synergistically to promote thrombus formation, especially in the setting of an underlying atherosclerotic disease. The presence of floating thrombus in a patient with clinical and MRI evidence of stroke represents a significant therapeutic dilemma and requires immediate decision about treatment.